Synaptic versus extrasynaptic NMDA receptor signalling: implications for neurodegenerative disorders - Hardingham, Giles E.; Bading, Hilmar (Nature reviews. Neuroscience, 2010)
NMDARs (N-methyl-D-aspartate receptors) have long been known for their role in neuropathology, and inappropriate activity is implicated in neuronal loss in acute disorders such as stroke and traumatic brain injury. Certain chronic neurodegenerative diseases are also associated with abnormal NMDAR activity, including Huntington's and Alzheimer's diseases. However, the destructive effects of NMDAR activity are in striking contrast to the observation that the survival and resistance to trauma of several neuronal types is boosted by physiological synaptic NMDAR activity and function. Thus, there is a dichotomy of NMDAR signalling.Recent studies have shown that cellular responses to NMDAR activation can depend on the receptor location. Activation of synaptic NMDARs, particularly when activated trans-synaptically, promotes neuronal health, whereas chronic activation of extrasynaptic NMDARs couples to cell death pathways. Differences are observed even when the overall Ca2+ loads triggered via the two routes are similar.Synaptic NMDAR activity strongly promotes neuronal health by initiating a programme of transcriptional changes that promote resistance to various traumatic stimuli. Synaptic NMDARs control a nuclear Ca2+-regulated multi-gene program that protects against excitotoxic and apoptotic insults. Transcriptional suppression of key components of the intrinsic apoptosis pathway also restricts the apoptotic potential of neurons. Moreover, synaptic NMDAR activity promotes resistance to oxidative insults by boosting intrinsic antioxidant defences through transcriptional changes of proteins encoding antioxidant genes and regulatory factors.Extrasynaptic NMDAR activity is coupled to several signalling pathways that promote neuronal death or vulnerability to trauma. These include the dephosphorylation and inactivation of the pro-survival transcription factor cyclic-AMP response element binding protein (CREB), nuclear import of the pro-death transcription factor forkhead box protein O (FOXO), inactivation of extracellular signal-regulated kinase 1/2 (ERK1/2) mitogen-activated protein (MAP) kinase, and calpain-dependent striatal enriched tyrosine phosphatase (STEP) cleavage and activation of p38 MAP kinase.A shift in the balance from synaptic towards extrasynaptic NMDAR signalling may be an important factor in the aetiology of neurodegenerative diseases. In Huntington's disease, mutant huntingtin causes a specific increase in extrasynaptic NMDAR currents. Furthermore, extrasynaptic NMDAR activity in turn promotes the toxicity of mutant huntingtin and synaptic NMDAR activity reduces mutant huntingtin toxicity by promoting the formation of non-toxic inclusions. In acute ischaemic trauma, cell death may be caused in part by an upregulation and activation of extrasynaptic NMDARsIn treating disorders associated with abnormal NMDAR activity, therapies aimed at selectively blocking chronic extrasynaptic NMDAR activity without interfering with normal synaptic NMDAR activity may be better tolerated and more efficacious than conventional antagonists. The NMDAR antagonist memantine is well suited to this role, which may explain its tolerance in humans and its recently demonstrated efficacy in preclinical models of Huntington's disease.
Published online 15 September 2010
Gesehen am 08.03.2023